2023
DOI: 10.1017/jns.2023.76
|View full text |Cite
|
Sign up to set email alerts
|

Associations of protein intake, sources and distribution on muscle strength in community-dwelling older adults living in Auckland, New Zealand

Anne N. Hiol,
Pamela R. von Hurst,
Cathryn A. Conlon
et al.

Abstract: Protein intake, sources and distribution impact on muscle protein synthesis and muscle mass in older adults. However, it is less clear whether dietary protein influences muscle strength. Data were obtained from the Researching Eating Activity and Cognitive Health (REACH) study, a cross-sectional study aimed at investigating dietary patterns, cognitive function and metabolic syndrome in older adults aged 65–74 years. Dietary intake was assessed using a 4-d food record and muscle strength using a handgrip streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Inadequate dietary intake may therefore be linked to the association between eating alone and decreased HGS. Although dietary protein intake was the lowest in both the men and women in our study, older women usually synthesize more muscle protein compared to that of older men [ 41 , 42 ]. It suggested that an increased rate of protein breakdown is related to more susceptibility to sarcopenia in women than men.…”
Section: Discussionmentioning
confidence: 95%
“…Inadequate dietary intake may therefore be linked to the association between eating alone and decreased HGS. Although dietary protein intake was the lowest in both the men and women in our study, older women usually synthesize more muscle protein compared to that of older men [ 41 , 42 ]. It suggested that an increased rate of protein breakdown is related to more susceptibility to sarcopenia in women than men.…”
Section: Discussionmentioning
confidence: 95%